Estimation of the price and income elasticities of residential electricity demand in Indonesia using household-level data - Jonathan Nainggolan (Jurnal Ekonomi dan Pembangunan, 2022)
This paper presents household-level econometric estimates of the income and price elasticities of residential electricity demand for Indonesia. Using annual household survey panel data of SUSENAS from 2011 to 2013, the estimation controls for household characteristics that significantly affect electricity consumption, such as demographic aspects, house size, and ownership of home appliances. The empirical results show that in Indonesia, the residential electricity is price- and income-inelastic, with price and income elasticities of -0.88 and 0.3, respectively. Urban residents use more electricity than their rural counterparts. Responding to the growing economy, the government should prepare a greater electricity capacity or induce a higher tariff to promote electricity savings.